Partial trisomy 20 (20q13) and partial trisomy 21 (21pter leads to 21q21.3). - Sanchéz, O (1977)
A patient with a double partial trisomy 20 and 21 with mild mental retardation and multiple congenital anomalies is presented. Despite trisomy for a substantial portion of chromosome 21, the patient showed only minor stigmata compatible with Down syndrome.